Prognostic effect of pulmonary hypertension in patients with chronic kidney disease: Univariate and multivariate analyses of factors associated with survival - Wang, Lei; Zhang, Wei; Zhang, Cailian; Yan, Zhe; Li, Shaomei; Zhang, Chunxia; Chen, Yakun; Pan, Qing; Liang, Xuzhi; Chen, Xian (Frontiers in Medicine, 2022)
Background: Prognostic effect of pulmonary hypertension (PH) in patients with chronic kidney disease (CKD) is not fully clear yet, this study was designed to elucidate baseline characteristics of CKD patients with different severities of PH, the association between kidney indicators and PH severity, and survival factors in CKD patients with PH. Methods: We extracted clinical data from electronic medical records of all patients diagnosed with PH in CKD from Jan 2016 to Dec 2020, and those with comorbid conditions causing PH were excluded. CKD stages were defined by estimated glomerular filtration rate thresholds. PH was defined as a systolic pulmonary artery pressure (sPAP) >35 mmHg estimated using echocardiograms. Demographics, clinical data, and test results were analyzed, and all-cause mortality data were obtained. Results: A total of 137 patients were included in the study. The mean age of the participants was 60 (42.5, 67) years, the mean sPAP was 58 (51, 69.5) mmHg, and 40.9% of the patients were women. Moderate PH group had more patients undergoing dialysis and higher frequency of coronary heart disease. Moderate-severe PH group had higher parathyroid hormone levels and lower low-density lipoprotein levels. Severe PH group had better kidney function parameters and lower serum phosphorus levels. PH severity had no direct relationship with CKD stages. In the univariate analysis, age and PH severity influenced survival. Multivariate analysis also showed independent prognostic effects for age and sPAP. Kaplan-Meyer curve intuitively displayed the survival differences among CKD patients with different PH severity. Predictor values of nomogram identified from survival analyses enabled calculation of death probabilities for CKD with PH patients. Nomogram was validated by ROC analysis. Conclusions: PH begins with early-stage CKD, and PH severity is not related to CKD progression. A higher pulmonary artery pressure and an older age are associated with an increased risk of death. Keywords: pulmonary hypertension, chronic kidney disease, clinical characteristics, survival